The fiscal review as a mechanism to guarantee the rights of the public treasury in Algeria An applied study of SAIDA Tax Center during the period 2014-2018 - Djebbouri, Mohamed; Ouessai, Rabah; Rahmani, Ahmed (Finance and Business Economies Review, 2019)
The purpose of this study is to highlight the role of audit fiscal in guaranteeing the rights of the public treasury by combating fiscal evasion and finding errors and omissions by taxpayers and correcting them in order to support the Algerian fiscal system, which is considered as a license giving the taxpayers the freedom to submit their periodic and annual tax statements. In order to establish a serious scientific approach to the problem of research, this study is intended to reflect the procedures of audit fiscal, which is a preventive and punitive measure. It stands in the face of the increasingly negative practices, based on the accounting audit as one of the most important mechanisms of the audit fiscal